Distinct Mitochondrial Remodeling During Mesoderm Differentiation in a Human-Based Stem Cell Model - Mostafavi, Sepideh; Balafkan, Novin; Pettersen, Ina Katrine Nitschke; Nido, Gonzalo S.; Siller, Richard; Tzoulis, Charalampos; Sullivan, Gareth J.; Bindoff, Laurence A. (Frontiers in Cell and Developmental Biology, 2021)
Given the considerable interest in using stem cells for modelling and treating disease, it is essential to understand what regulates self-renewal and differentiation. Remodeling of mitochondria and metabolism, with the shift from glycolysis to oxidative phosphorylation (OXPHOS), play a fundamental role in maintaining pluripotency and stem cell fate. It has been suggested that metabolic 'switch' from glycolysis to OXPHOS is germ-layer specific as during early ectoderm commitment, glycolysis remains active while during the transition to mesoderm and endoderm lineages, it is downregulated. How mitochondria adapt during these metabolic changes and whether mitochondria remodeling is tissue specific remains unclear. Here we address the question of mitochondrial adaption by examining the differentiation of human pluripotent stem cells to cardiac progenitors and further to functional cardiomyocytes. Contrary to recent findings in neuronal differentiation, we found that mitochondrial content decreases continuously during mesoderm differentiation, despite clear mitochondrial remodeling giving increased mitochondrial activity and higher levels of ATP-linked respiration. Thus, our work both highlights similarities in mitochondrial remodeling during the transition from pluripotent to multipotent state in ectodermal and mesodermal lineages, while at the same time demonstrating cell-lineage-specific adaptions upon further differentiation. Our results improve understanding of how mitochondria remodeling and the metabolism interact during differentiation and show that it is erroneous to assume that increased OXPHOS activity during differentiation requires a simultaneous expansion of mitochondrial content.